The influence of the number of free surfaces on the energy distribution and attenuation law of blasting vibration signals from peripheral holes: field experiment and simulation - Lan, Riyan; Wang, Zhen; Lu, Jianyou; Zhou, Zilong; Chen, Lu; Gao, Shan (Frontiers in Earth Science, 2023)
Tunnels are commonly excavated using drilling and blasting methods, and the surrounding rock is greatly affected by the vibration of surrounding hole blasting. To study the influence of the number of free surfaces on the energy distribution and attenuation law of surrounding hole blasting vibration signals, on-site experiments and numerical simulation experiments were conducted. The research results indicate that the higher the number of free surfaces, the smaller the peak vibration velocity. The longitudinal Fourier main frequency decreases with the distance from the monitoring point. The more free surface, the greater the centroid frequency and zero crossing frequency. In addition, numerical simulation shows that the degree of rock fragmentation after blasting increases with the increase of the number of free surface of rock.